Diagnostic Hematology - Beck, Norman. (Springer London : Imprint: Springer, 2009)
Hematology is sometimes regarded as a purely laboratory subject, but is a clinical specialty in its own right. Understanding hematology requires insight into several distinct aspects: applied physiology, understanding the essential pathological processes of the blood, and the laboratory aspects. Nevertheless, there is no substitute for the clinical approach in the final assessment and management of any patients disease, of whatever nature, and therefore, independent of any diagnostic test, the final evaluation and judgment must come from the clinician. Diagnostic Hematology approaches the topic from the clinical decision-making perspective. It stresses the importance of effective, patient-centered care of hematological patients, requiring a comprehensive clinical insight into the disease processes, and thus provides an integrated clinical and pathological approach. Considerable emphasis is placed on obtaining the clinical history and examination, and the interpretation of the clinical patterns that are exposed from the ever increasing number of laboratory tests available. All the practical essentials are covered, ensuring that this book contains the vital clinical information needed by all physicians involved in hematological diagnoses.